Astaxanthin Production in Haematococcus pluvialis Under Lead Nanoparticle Stress in Different pH and Salinity Conditions - Ramburuth, Shardhavi (2016)
Haemaatococcus pluvialis is a unicellular fresh water microalga which has the highest amount of antioxidant compared to other microorganisms. It is also rich in astaxanthin, which is a carotenoid. Astaxanthin is extremely beneficial to food, pharmaceutical, nutraceutical and cosmetic industry. This is because of its very high antioxidant activity which is very much more than vitamin C and green tea etc. Since it is so desirable by so many companies, it should be produced in large amounts. In this experiment, a new method of accumulating astaxanthin from H. puvialis is tested which is the use of lead nanoparticle in order to find the ideal condition for maximum astaxanthin production. The H. pluvialis was cultured and then subcultured in different pH and salinity conditions. The culture at the condition where there has been maximum cell growth was obtained which is pH 7 and salinity 0.25%. The optimum culture condition obtained was used to grow the H. pluvialis and the culture was subjected to lead nanoparticle stress. The astaxanthin was then extracted using the HCI-ACE method and its concentration was measured using the spectrophotometer at 480 nm. There was maximum astaxanthin production at 10ppm and therefore lead nanoparticle can be used as stimulatory for growth.